Potentials of bentonite enhanced termite mound soil for bottom lining in waste containment system - Omobolaji Taofeek Opafola; Adebola A Adekunle; Adedayo Adekunle Badejo; Olayemi Johnson Adeosun (Brawijaya University, 2020)
The sole purpose of a compacted landfill liner is to contain and mitigate the impact of leachate on the environment. This research assessed the engineering properties of bentonite enhanced termite mound mixture to ascertain their suitability as an alternate landfill liner. The mixture of mound soil and bentonite was proportioned by percentage weight as (100:0), (95:5), (90:10) and (85:15) respectively. The compaction analysis reveals an optimum moisture content ranging from 13.80% to 18.52% and a maximum dry density that varied from 1.72 g/cm3 to 1.88 g/cm3. The hydraulic conductivity result of 15% bentonite-mound soil mixture (0.23 x 10-9 m/s) established hydraulic conductivity less than 1 x 10-9 m/s, which satisfied the criteria for landfill liner. Hence, a mixture of 15% bentonite enhanced mound soil is found suitable as an alternate bottom liner.